DIGITAL PLATFORM IN AGRICULTURE – AN EVALUATIVE STUDY OF INFORMATION AND ITS UTILITY BY THE FARMERS - P. RADHIKA, K.SHRAVANI, N. SIVARAMANE and (The Journal of Research, PJTSAU, 2019)
An Information and Communication Technology (ICT) in agriculture is an emerging field focusing on the enhancement of agricultural and rural development in India. ICTs offer a great opportunity to facilitate the flow of information and technology services delivery especially to the farmers (Maningas, 2006). Information pertaining to sowing, soils, price and pests and diseases control helps farmers to take better decisions in farm activities. At present, there are many ICT initiatives by government, nongovernment and private organizations in the field of agriculture (Anupindi, 2003). ICT projects like Kisan Call Center, e-Choupal, IFFCO Kisan Sanchar Limited, Farmers’ Portal, mKisan and iKisan, etc. Digital Platform in Agriculture (DPA) is launched by a private company (eFresh Agribusiness pvt ltd.) in Telangana, Andhra Pradesh, Maharashtra, Karnataka, Gujarat, Tamilnadu and Punjab in India.